The Influence of Organizational Commitment, Conflict Resolution Skills, Safety Climate for Safety Accidents On Manufacturing Industry in East Java Province. - Arnol, Yusuf; Brahmasari, Ida Aju; Nugroho, Riyadi (Archives of Business Research, 2018)
This research aims to analyze the influence of organizational commitment, conflict resolution skills, safety climate for safety accidents in manufacturing industry in East Java Province. This research uses survey method conducted on all employees of production division from steel factory companies amounting to 162 employees. The number of samples used as much as 115 respondents obtained from the formula Slovin. Data analysis and hypothesis in this research using Structural Equation Modeling (SEM) with AMOS 20.0 software. The results of this study indicate that three hypotheses are accepted. The significance of this hypothesis suggests indirectly but through safety climate mediation, so the skills of production division workers in preventing accidents will increase